2022
DOI: 10.3390/ijerph192013565
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Conscientiousness and Well-Being among Chinese Undergraduate Students: A Cross-Lagged Study

Abstract: Chinese culture attaches great importance to the education and cultivation of youth conscientiousness, however in the context of Chinese culture, little is known about the relationship between conscientiousness and mental and physical health. The present study aimed to investigate whether there is a reciprocal relationship between conscientiousness and well-being (subjective and physical well-being) among Chinese undergraduate students. A series of self-reported questionnaires were administered to 365 undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…A total of 124 items from four scales at T1 were subjected to the exploratory factor analysis without rotation and the analysis produced 33 common factors, with the rst explaining the 25.48% variance. The analysis of 124 items at T2 yielded 38 factors, with the rst explaining the 22.48% variance, both of which were lower than the critical standard of 40% 34 . The results indicated that the correlation between the studied variables in this study was not driven purely by method bias.…”
Section: Assessment Of Common Methods Biasesmentioning
confidence: 89%
“…A total of 124 items from four scales at T1 were subjected to the exploratory factor analysis without rotation and the analysis produced 33 common factors, with the rst explaining the 25.48% variance. The analysis of 124 items at T2 yielded 38 factors, with the rst explaining the 22.48% variance, both of which were lower than the critical standard of 40% 34 . The results indicated that the correlation between the studied variables in this study was not driven purely by method bias.…”
Section: Assessment Of Common Methods Biasesmentioning
confidence: 89%
“…Hu et al, 2021; Y. Hu et al, 2022; Shek et al, 2017; Xu et al, 2016; Yu et al, 2018). One text employed experimental research with the aim of evaluating the effectiveness of positive online psychological intervention (PPI) in the context of well-being (Auyeung & Mo, 2019), as well, one text presented the results of research conducted in a quasi-experimental design determining the impact of service learning (SL) on spiritual well-being and mental health (Pong, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In the studies analyzed, the authors sought answers about the relationship between well-being and traits such as resilience, coping styles (Chen, 2016), flow (Wu et al, 2021), playfulness (Y. Li et al, 2021), kindness (Datu & Lin, 2022) or conscientiousness (Y. Hu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations